Echinatin effectively protects against NLRP3 inflammasome–driven diseases by targeting HSP90 - Xu, Guang (JCI Insight, 2021)
Aberrant activation of NLRP3 inflammasome has been implicated in a variety of human inflammatory diseases, but currently, no pharmacological NLRP3 inhibitor has been approved. In this study, we showed that echinatin, the ingredient of the traditional herbal medicine licorice, effectively suppresses the activation of NLRP3 inflammasome in vitro and in vivo. Further investigation revealed that echinatin exerts its inhibitory effect on NLRP3 inflammasome by binding to heat-shock protein 90 (HSP90), inhibiting its ATPase activity and disrupting the association between the cochaperone SGT1 and HSP90-NLRP3. Importantly, in vivo experiments demonstrated that administration of echinatin obviously inhibits NLRP3 inflammasome activation and ameliorates LPS-induced septic shock and dextran sodium sulfate–induced (DSS-induced) colitis in mice. Moreover, echinatin exerted favorable pharmacological effects on liver inflammation and fibrosis in a mouse model of nonalcoholic steatohepatitis (NASH). Collectively, our study identifies echinatin as a potentially novel inhibitor of NLRP3 inflammasome, and its use may be developed as a therapeutic approach for the treatment of NLRP3-driven diseases.